2013
DOI: 10.1016/j.brat.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing depression in 9–10 year old children in low SES schools: A longitudinal universal randomized controlled trial

Abstract: The Aussie Optimism: Positive Thinking Skills Program (AOP-PTS) is an innovative curriculum-based mental health promotion program based on cognitive and behavioural strategies. The program is aimed at preventing depressive and anxiety symptoms and disorders in middle primary school children aged 9-10 years. Students from 22 low SES primary schools (N = 910) were randomly assigned to an intervention or a control group and assessed at baseline, post-test, 6 months and 18 months. The intervention group received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
3
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 53 publications
5
65
3
3
Order By: Relevance
“…In a small randomized controlled trial (pilot study), delivered by psychologists, Rooney et al (2006) found the AOP-PTS was associated with significant reductions in depressive symptoms and more positive attributions at post-test, as well as fewer depressive disorders at 9 month follow-up. Further, a larger randomized control study (Rooney et al, 2013), involving 22 low SES primary schools in the Perth metropolitan region, supported the earlier findings. In this larger trial, the program was delivered by teachers to year 4 and 5 children.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…In a small randomized controlled trial (pilot study), delivered by psychologists, Rooney et al (2006) found the AOP-PTS was associated with significant reductions in depressive symptoms and more positive attributions at post-test, as well as fewer depressive disorders at 9 month follow-up. Further, a larger randomized control study (Rooney et al, 2013), involving 22 low SES primary schools in the Perth metropolitan region, supported the earlier findings. In this larger trial, the program was delivered by teachers to year 4 and 5 children.…”
Section: Introductionsupporting
confidence: 68%
“…Due to attrition, the sample sizes for data collected at 42 and 54 months was 190 and 180 respectively. Child gender was not reported by 27 (14%) and 34 (19%) cases at 42 and 54 month follow-up, respectively; however, as earlier reports of this intervention (up to 18 month follow-up) found no significant gender by group by time interaction (Rooney et al, 2013), gender was not expected to impact on the 42 and 54 month follow-up results. Whilst the previous study also obtained clinical diagnoses for children at or beyond clinical cut-off on symptom measures, such information was not collected for the current study due to lower numbers.…”
Section: Methodscontrasting
confidence: 52%
See 2 more Smart Citations
“…However, the findings of large-scale prevention studies in schools using group CBT [57], bibliotherapy [57,58], group CBT focused on positive thinking [59], and social skills training [60] have not been promising. Supporting the importance of parenting and the family environment, a recent program to improve resiliency skills and positive school support successfully reduced depressive and anxiety symptoms only in youth who experienced poor family support [61].…”
Section: Interventionmentioning
confidence: 98%